Europa Decapitates her Seducer with a Euro Sign - Zantides, Evripides (My University, 2012)
The Posters of Discontent II was an exhibition in 2012 featuring the work of 19 political poster designers from 10 countries. Curated by Professor Andrew Maniotes, this exhibition was shown at University Gallery, Eastern Michigan University.
Keywords: Campaign; Unity; Policy enforcement; Protest--political posters; Politics